PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP PENGAWASAN BANK (Studi Kasus Pada Bank Pembangunan Daerah Seluruh Indonesia) - Annisa, Syarifah Farra; Anugrah, Rita; Nurmayanti, Poppy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
The aim of this research is to show whether there issignificant effect of competence, independence and integrity toeffectiveness of bank supervision. The object of this research are thebanking company incorporated in the Regional Development Bank(BPD) throughout Indonesia. The respondents are individuals at theaudit committee team on Regional Development Bank (BPD)throughout Indonesia. The research method that was used ishypothesis testing with correlation analysis. Data collection in thisresearch was by sending questioners directly and also by mail survey.From the 81 questioners only 40 questioners was returned, thereforethe data was tested 40 respondents. The hypothesis test was by singmultiple regression method. The research find that there is nosignificant effect of competence and independence audit committee toeffectiveness of bank supervision, however there is significant effect ofintegrity to effectiveness of bank supervision.